Direct Visualization of Arterial Emboli in Moyamoya Syndrome - Shulman, Julie G.; Snider, Samuel; Vaitkevicius, Henri; Babikian, Viken L.; Patel, Nirav J. (Frontiers in Neurology, 2017)
Background: Hemodynamic insufficiency is often considered the cause of ischemic stroke in patients with moyamoya syndrome. While high-intensity transient signals (HITS) on transcranial Doppler (TCD) have been reported in this population, the relationship between these signals and ischemic symptoms is not clearly established. Accordingly, current treatment is directed at improving perfusion. Clinical Presentation: We present two patients with symptoms of cerebral ischemia and angiographic findings of moyamoya syndrome. In each case, ischemia may have been caused by either hypoperfusion or embolization. Patient A presented with multifocal right middle cerebral artery (MCA) territory infarctions and angiographic findings consistent with moyamoya disease. She underwent right superficial temporal artery (STA)-MCA bypass. Intra-operatively, embolic material was observed and recorded traveling through the recipient MCA branch artery on two occasions. Post-operative TCD demonstrated HITS that resolved with uptitration of antiplatelet therapy. Patient B presented with multifocal, embolic-appearing left MCA infarctions and unilateral angiographic moyamoya syndrome. She was found to have HITS in the left MCA, which eventually resolved with a combination of antiplatelets and anticoagulation. Conclusion: Hemodynamic compromise may not be the only cause of brain infarction in patients with moyamoya syndrome. Observations from these two patients provide both direct visualization and TCD evidence of embolization as a potential etiology for brain ischemia. Future investigations into the role of antithrombotic agents should be considered.